The Cyclic Decomposition of cf(Q_28×C_p)/ R ̅(Q_28×C_p) - Naseer Albakaa; Habeeb Al-Bdairi; Neeran Abd Alameer (Journal of Kufa for Mathematics and Computer, 2022)
In this paper, we propose the cyclic decomposition of the factor group cf(Q_28×C_p),Z)/R ̅(Q_28×C_p ), and the group cf(Q_28×C_p ) is Z-valued class functions of the direct product group (Q_28×C_p ) under the operation of addition, and R(Q_28×C_p )is the subgroup of the generalized characters of the group cf(Q_28×C_p,Z).Then cf(Q_28×C_p )/(Q_28×C_p ) is an abelian factor group denoted by K(Q_28×C_p ) when Q_28 the quaternion group |Q_28 |=56, and|C_p |=p. Also, we find the rational valued characters table of the group (Q_28×C_p ) when p is prime numbers is given as following: